Analyzing the Impact of Soft, Stimulating and Depressing Songs on Attention Among Undergraduate Students: A Cross-Sectional Pilot Study in Bangladesh - Begum, Mst. Marium; Uddin, Md. Sahab; Rithy, Jannatul Ferdaush; Kabir, Janisa; Tewari, Devesh; Islam, Azharul; Ashraf, Ghulam Md. (Frontiers in Psychology, 2019)
Music is strongly linked to attention and giving attention can boost intelligence. The purpose of this study was to scrutinize the impact of soft, stimulating, and depressing songs on the attention of students. The study was performed on 280 undergraduate students. Students were divided into 4 groups (i.e., control, soft, stimulating, and depressing) and subjected to 3 songs, soft (That’s My Name), stimulating (Rain Over Me) and depressing (Broken Angel) songs. The Uddin’s Numeral Finding (NF) and Typo Revealing (TR) tests were used to analyze the attention of the students. In the NF, 75.54% attention was exerted by students subjected to stimulating song followed by soft song’s group (i.e., 74.32%) with respect to control group. Amid all groups, the lowest percentage, 70.77% of attention was reported for students subjected to the depressing song. For TR test, stimulating song’s group exerted highest, 45.97% attention, soft song’s group exerted 45.27%, control group exerted 42.70%, and lowest (i.e., 41.54%) attention was exerted by depressing song’s group. In NF test, concerning sex, amid male and female, male exerted higher (77.04%) attention than female but for TR test female exerted higher (i.e., 48.15%) attention for students subjected to stimulating song. Regarding the age of the study in case of NF test for stimulating song’s group, 18–20 years age students exerted highest, 82.07% attention but for TR test highest, 48.75% attention was reported for 23–25 years age students. For NF test, regarding the age of the study 1st-year student exerted highest, 92.44% attention but for TR test highest, 57.33% attention was reported for 3rd-year students for stimulating song’s group. Concerning residential status in both NF and TR tests, for students lived with family subjected to stimulating song exerted highest, 77.93% and 48.6% attention, respectively with respect to students lived without family and remaining groups. This study suggested that song influences the neuronal circuits linked to alert and cognitive functions and the stimulating song has the acme power of increasing attention while depressing song reduces the attention. Therefore, the exciting song can be an operative intervention for enhancing attention, cognitive functions, and treatment of associated neuropsychological disorders.